A Historical and Heritage Studies of indigenously-owned business in Post-colonial Lesotho : politics constraints marginalisation and survival. 1966-2012 - Mlambo, Alois S. (University of Pretoria, 2016)
Thesis (PhD)--University of Pretoria, 2015.